Biomechanical Influences on Mesh-Related Complications in Incisional Hernia Repair - Kallinowski, Friedrich; Ludwig, Yannique; Gutjahr, Dominik; Gerhard, Christian; Schulte-Hörmann, Hannah; Krimmel, Lena; Lesch, Carolin; Uhr, Katharina; Lösel, Philipp; Voß, Samuel; Heuveline, Vincent; Vollmer, Matthias; et al. (Frontiers in Surgery, 2021)
Aim Incisional hernia repair creates a composite of the abdominal tissues with a textile mesh. Recurrence indicates a bond between tissue and mesh too weak to withstand physical activity durably. The weak bond is mechanically overloaded early. Non-crosslinked collagen stretches and results in an occult fascial dehiscence. A continuously overburdened healing process manifests at a later stage as a recurrent hernia defect. Which biomechanical factors can strengthen the mesh-tissue interface? How can surgeons enhance the bond between mesh and tissue? Material and methods Strength of the mesh-tissue interface can be assessed by dynamic loads delivered by a self-built bench test. The test simulates coughing and is called dynamic impact strain. Strength limits are based on tissue influences and material properties of hernia meshes and fixation devices. The influences and the properties are condensed in coefficients representing their relative retention power. The relative strength can be related to stochastic failures rates once the strain and the elasticity of the individual human abdominal wall are known. The tissue quality of the individual patient is determined with computerized tomography at rest and during Valsalva’s maneuver before surgery. With this information, durable repairs can be designed. the gained resistance should surpass the critical retetion force. Results The strain observed in porcine, bovine and human tissue is in the same range. Tissue samples exhibit both brittle and ductile failure patterns. Accordingly, sutures show loosening or burst at vulnerable points. Both the load duration and the peak load increases destruction. Stress concentrations elevate failure rates. Regional areas of force contortions increase stress concentrations. Hernia repair betters strain levels without eliminating it. Measures to heal the detrimental strain effects include closure of the defect, use of higher DIS class meshes, increased mesh overlap and additional fixation. Surgeons can vary their repair and choose the safety margin of the reconstruction as desired. Conclusion Using the concept of a critical and a gained resistance towards pressure related impacts, a durable hernia repair can be designed from available coefficients. With the guidance of biomechanical principles, surgeons can prevent mesh-related complications such as hernia recurrence in incisional hernia repair.